**If a**^{2} + b^{2} = 13 and ab = 6, find

^{2}+ b

^{2}= 13 and ab = 6, find

(i) a + b

(ii) a – b

**Answer :**

##### (i) We know that

**(a + b) ^{2} = a^{2} + b^{2} + 2ab**

Substituting the values

= 13 + 2 × 6

So we get

= 13 + 12

= 25

Here

a + b = ± √25 = ± 5

##### (ii) We know that

**(a – b) ^{2} = a^{2} + b^{2} – 2ab**

Substituting the values

= 13 – 2 × 6

So we get

= 13 – 12

= 1

Here

a – b = ± √1 = ± 1

**More Solutions:**

- If x + y = 6 and x – y = 4, find
- If x – 3 = 1/x, find the value of x2 + 1/x2.
- If x + y = 8 and xy = 3 ¾, find the values of
- Find the value of 2 (x + y)2 + (x – y)2.
- If a – b = 3 and ab = 4, find a3 – b3.
- Find the value of 8a3 – 27b3.
- If x + 1/x = 4, find the values of
- If x – 1/x = 5, find the value of x4 + 1/x4.
- If x – 1/x = √5, find the values of
- If x + 1/x = 6, find